2020
DOI: 10.1002/jcp.29516
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum distribution during bovine oocyte activation is regulated by protein kinase C via actin filaments

Abstract: Fertilization‐induced [Ca2+]i oscillations generally depend on the release of calcium ions from the endoplasmic reticulum (ER). Since ER is the main store of calcium ions, it plays an important role in oocyte fertilization. However, the mechanism of ER organization at oocyte activation is unknown. Here, we show that protein kinase C (PKC) is involved in ER distribution during bovine oocyte activation, but not involved in cell cycle resumption and spindle organization. Actin filaments were affected by PKC pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Here we show that treatment with a low concentration of palmitic acid increases the area of SER polygons. Similarly, actin filaments have a conserved role in maintenance of the ER network [35,64,65] and treatment with the actin-depolymerising drug cytochalasin B alters ER content in developing oocytes (resulting in ER accumulation at the cortical region during oocyte activation) [37,66]. Consistent with this, our pipeline was able to detect that brief treatment with cytochalasin B induces ER reorganisation with a significant increase in the area of SER polygons.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Here we show that treatment with a low concentration of palmitic acid increases the area of SER polygons. Similarly, actin filaments have a conserved role in maintenance of the ER network [35,64,65] and treatment with the actin-depolymerising drug cytochalasin B alters ER content in developing oocytes (resulting in ER accumulation at the cortical region during oocyte activation) [37,66]. Consistent with this, our pipeline was able to detect that brief treatment with cytochalasin B induces ER reorganisation with a significant increase in the area of SER polygons.…”
Section: Discussionsupporting
confidence: 79%
“…Several studies have reported alteration of ER organisation by different chemical compounds [32,37,49]. A limitation of all these studies however is that they employed qualitative analysis and did not enable an objective description of the changes observed.…”
Section: Drug-induced Er Reorganisation In U-2 Os Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This subclass is known to have an important role in oocyte maturation, meiotic resumption, and fertilization [89][90][91]. Protein kinase C modulates intracellular calcium oscillations, within the oocyte, following fertilization, leading to cortical granule release and a subsequent polyspermy block [90][91][92]. Calcium oscillations at the time of fertilization have also been demonstrated to increase mitochondrial ATP production to support metabolic requirements of fertilization [93].…”
Section: Oocyte Transcriptomementioning
confidence: 99%
“…Additionally, the cortical region of mature oocytes, characterized by cluster formation, showed a similar distribution pattern between UF-VIT and control group. These clusters contain inositol 1,4,5-trisphosphate (IP 3 ) receptors (IP 3 R1), which are activated by sperm entry and play a role in [Ca 2+ ]i release and periodic calcium oscillation, thus contributing to oocyte activation (15,(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%